Per se performance of elite coconut genotypes and hybrids for economic quality traits and oil yield - Subramanyam, Praneetha; R, Sudha; S, Nivitha; R, Suriya; R, Mahalakshmi (International Coconut Community Journal, 2023)
The present study was conducted at Coconut Research Station, Aliyarnagar Tamil Nadu state of India. The experimental trees comprised of five tall coconut genotypes viz., IC 610370, IC 610371, IC 610372, IC 610374 and IC 610379 West Coast Tall (Check), and the hybrids viz., Chowghat Orange Dwarf x Aliyar 1 (COD x ALR1), Chowghat Orange Dwarf x West Coast Tall (COD x WCT), Aliyar 1 x Malayan Green Dwarf (ALR1 x MGD), Malayan Green Dwarf x Aliyar 1 (MGD x ALR), Kenthali Dwarf x Aliyar 1 (KTD x ALR1) and Veppankulam Hybrid Coconut VHC 2 (Check hybrid - released from Veppankulam Coconut Research Station, Tamil Nadu Agricultural University, Tamil Nadu, India). Coconut palms of uniform size were taken from the chosen genotypes and hybrids for recording the observation. All the coconut genotypes and hybrids showed variation in yield, nut characters, and quality traits. The results of the present study revealed that the genotype IC 610370 and the hybrid COD x WCT recorded maximum values for all the recorded traits. This was followed by the genotype IC 610371 and the hybrid COD x ALR1.